2015
DOI: 10.1007/s11270-015-2536-x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated herbicides in fish, birds and mammals in the Baltic Sea

Abstract: The aim of the present work was to determine the concentration levels, as well as accumulation and magnification coefficients, of triazine derivatives in herring gulls and Baltic grey seals 11 years after a ban on their use in the EU and eight after their exclusion in Poland. Dead birds were collected in the coastal zone of the Gulf of Gdansk in the years 2010–2012. The grey seals, on the other hand, were from before 2007, when s-triazine derivatives were still in use. Triazine herbicides (atrazine, simazine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…We also found pathways in the core metabolism that are involved in the degradation of persistent pollutants and plastics such as atrazine [65], bisphenol [66], and chlorobenzene [67] (S6 Table). The accumulation of harmful substances has been reported in the tissues of marine mammals [68], with the degradation of these toxic compounds mainly depending on the metabolism of bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…We also found pathways in the core metabolism that are involved in the degradation of persistent pollutants and plastics such as atrazine [65], bisphenol [66], and chlorobenzene [67] (S6 Table). The accumulation of harmful substances has been reported in the tissues of marine mammals [68], with the degradation of these toxic compounds mainly depending on the metabolism of bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Liver is an essential organ involved in the metabolism of exogenous toxic substance and also a primary target of ATR toxicity. It is known to cause hepatic damage in frogs, fish, birds, pigs, and rodents . The use of histologic and ultrastructural analysis allowed for the damage of target organelle in the microsomes by exposure to ATR .…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, atrazine can induce pathological effects in multiple tissues [ 7 , 12 ]. Atrazine was recorded in the liver and heart [ 46 - 49 ], suggesting the heart and liver are organs involved in the metabolism of atrazine. Our previous study showed that atrazine induced significantly ionic disorder in the liver and heart on mice as well [ 18 , 30 ].…”
Section: Discussionmentioning
confidence: 99%